2012
DOI: 10.3171/2011.12.spine11636
|View full text |Cite
|
Sign up to set email alerts
|

Spinal arteriovenous malformation associated with spinal metameric syndrome: a treatable cause of long-term paraplegia?

Abstract: Cutaneomeningospinal angiomatosis, or Cobb syndrome, is a rare metameric developmental disorder presenting as an extradural-intradural vascular malformation that involves bone, muscle, skin, spinal cord, and nerve roots. A 14-year-old girl with a red nevus involving the T6–9 dermatomes on the left side of her back presented with a 5-year history of bowel and bladder incontinence, paraplegia, and lower-extremity sensory loss. Magnetic resonance imaging demonstrated a hemangioma in the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…[356] Most of the cases reported “typical” presentation of angiomatous-cutaneous stains and spinal AVM corresponding to the same metamere, whereas other cases reported Cobb syndrome cases with cutaneous cavernous angiomas (CAs) associated with spinal Cas. [9] A few cases have been presented as acute paraplegia, but none as acute quadriparesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[356] Most of the cases reported “typical” presentation of angiomatous-cutaneous stains and spinal AVM corresponding to the same metamere, whereas other cases reported Cobb syndrome cases with cutaneous cavernous angiomas (CAs) associated with spinal Cas. [9] A few cases have been presented as acute paraplegia, but none as acute quadriparesis.…”
Section: Discussionmentioning
confidence: 99%
“…[9] A few cases have been presented as acute paraplegia, but none as acute quadriparesis. [1610] Although the most widely accepted diagnosis criteria is that proposed by Kissel and Dureux,[4] which includes a skin nevus in the same segment as the spinal angioma (with or without visceral angiomatosis), the type and pathology of spinal angioma is still ill-defined. The genetic framework of this syndrome also remains unclear, although one study suggested an inherited disposition based in a family case of Cobb syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4]8,10,[12][13][14][20][21][22][23][24][25]29,[32][33][34][35][36][37]39,[41][42][43]45,48,50 For these 51 patients, the mean age at presentation was 15.0 ± 10.5 years (± SD), and there was a slight male sex predilection (63% male, 1.7:1 male/ female ratio) ( Table 2). Presentation modalities included progressive neurological deficits in 35% of cases, acute hemorrhage in 31%, an acute neurological deficit without hemorrhage in 22% of cases, and incidental discovery in the remaining 12%.…”
Section: Resultsmentioning
confidence: 99%
“…7,13,18 Gross et al reviewed 27 publications and analyzed 352 cases of intramedullary spinal cord CAs. 7 They reported that the mean age at presentation was 42 years, without sex predominance.…”
Section: Discussionmentioning
confidence: 99%